2021
DOI: 10.1111/jan.14928
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of nurse‐led interventions to prevent childhood and adolescent overweight and obesity: A systematic review of randomised trials

Abstract: Background Obesity among children and adolescents continues to rise worldwide. Despite the efforts of the healthcare workforce, limited high‐quality evidence has been put forward demonstrating effective childhood obesity interventions. The role of nurses as primary actors in childhood obesity prevention has also been underresearched given the size of the workforce and their growing involvement in chronic disease prevention. Aim To examine the effectiveness of nurse‐led interventions to prevent childhood and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Thirty-one SRs were included in this umbrella review . SRs examined nutrition interventions for pediatric obesity prevention in all settings combined [20,22,30,33,34,43,44,47] or in the home and family [20,22,35], healthcare [22,37,49,50], school [20,22,23,25,[27][28][29]36,38,[40][41][42]46], or community settings [21,22], or examined the efficacy of food assistance programs [24,26,27,31,32,39] or electronic interventions [45,48]. The study selection process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one SRs were included in this umbrella review . SRs examined nutrition interventions for pediatric obesity prevention in all settings combined [20,22,30,33,34,43,44,47] or in the home and family [20,22,35], healthcare [22,37,49,50], school [20,22,23,25,[27][28][29]36,38,[40][41][42]46], or community settings [21,22], or examined the efficacy of food assistance programs [24,26,27,31,32,39] or electronic interventions [45,48]. The study selection process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…45,50,51 For example, nurses are already involved in the prevention of chronic disease 69 and are well placed to play an important part in childhood obesity prevention. 70 Thus, implementation strategies should also consider the role of broader health workforce and how they could contribute to effective execution.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is acknowledged that other healthcare professionals can play an important role in childhood obesity prevention, and several CPGs in this review specifically highlighted the importance of multidisciplinary teams 45,50,51 . For example, nurses are already involved in the prevention of chronic disease 69 and are well placed to play an important part in childhood obesity prevention 70 . Thus, implementation strategies should also consider the role of broader health workforce and how they could contribute to effective execution.…”
Section: Discussionmentioning
confidence: 99%
“…During growth, an increase of one or two curves of weight should be considered as a potential trend towards obesity. Several studies demonstrated that interventions involving nurses to treat childhood obesity led to significant reductions in BMI, and BMI percentiles 50,51 .…”
Section: Nursing Care For Childhood Obesitymentioning
confidence: 99%